Detection of Fertility Levels of Female Bawean Deer (Axis kuhlii) Based on Fecal Steroid Metabolic - Rahmawati, Mitha Ardila; Hariadi, Mas'ud; Restiadi, Tjuk Imam; Rimayanti, Rimayanti; Lestari, Tita Damayanti; Srianto, Pudji (Universitas Airlangga, 2021)
The aim of the study was to detect the fertility level of females Bawean deer (Axis kuhlii) through fecal steroid metabolic which were tested using Enzyme-Linked Immunosorbent Assay (ELISA). The study used five females Bawean deer in Taman Flora Surabaya, which were marked using R1, R2, R3, R4, and R5 necklaces. The feces of each deer was collected on the 1st day, 6th day, 11th day, 16th day, and 21st day. The samples which were collected then extracted using the freeze dry method. Samples were tested using ELISA. The results of the measurement of the levels of fecal steroid metabolic in five Bawean deers showed that three Bawean deer (R1, R4, and R5) were in the luteal or pregnant phase as indicated by the increased of progesterone from 1st day to 21st day. While the other two Bawean deer (R2 and R3) were in the follicular or estrous phase as indicated by the decreased of level of faecal steroid metabolic on 11th day for deer R2 and 16th day for deer R3. The results showed that the levels of the fecal steroid metabolic can be used to determine the follicular phase and luteal phase and the pregnancy status of female Bawean deer.